Evaluación agronómica de los maíces híbridos ‘pioneer 30f87’, ‘pioneer 30k75’ e ‘iniap 602’ como testigo en presencia de varios niveles de fertilizacion, en condiciones de secano. - Villamar Palma, Juan Antonio (2011)
In the land of Mr. Ignacio Nicola, located in Precinct Puerto Pechiche, Canton Ventanas, Los Rios Province, was established a trial in maize hybrid 'Pioneer 30F87', 'Pioneer 30K75' and 'Iniap H-602', trying different levels of chemical fertilizer to achieve high yields of 7, 8, 9 and 10 tonnes of maize per hectare, in order: a). Evaluate the agronomic performance and grain yield of hybrids tested in dry conditions, b). Determine the appropriate program of chemical fertilizer to exploit the genetic potential of hybrid corn, c). Identify the larger capacity hybrid maize grain production, d). Economically analyzing grain yield according to the costs of treatment. Experimental design was used "randomized complete block, with 3 x 4 factorial arrangements in four replications, giving a total of 12 treatments. The experimental plot consisted of 4 rows of 6 m long, 0.70 m apart, giving an area of 16.8m2. The useful area of the experimental plot of 8.4m2, ie delete a row on each side by the edge effect.